Improving Marketing Performance Through Customer Engagement Building - Syafrudin Yusuf, M.; Limakrisna, Nandan; Muharam, Hari (Journal of World Science, 2022)
Introduction: This study aims to examine the effect of the Customer Engagement dimension on Marketing Performance using the SEM model, as well as provide information in the form of analysis results that can be used by private banking companies to improve marketing team performance through customer engagement. Method: This research is quantitative research with the help of Lisrel software. The data collection technique was carried out by survey method. The data collection instrument was a questionnaire which was distributed online to 400 customers of private banks in the Greater Jakarta area. Result: The results show that all hypotheses are acceptable, the four dimensions of customer engagement namely Absorption, Dedication, Vigor, and Interaction have a significant effect on customer engagement. Customer engagement has a significant effect on marketing performance. Marketing performance has a significant effect on the company's financial and non-financial profits. Conclusion: This research has the meaning of being able to provide information in the form of analysis results that can be used by private banking companies to improve the performance of the marketing team through customer engagement.